Lift above Poverty Micro-Finance Bank, Rural-Women Financial Security and Crime Reduction Strategies in Nigeria: Evaluation of Selected Communities in Badagry, Lagos State, Nigeria - Abdullahi, Haruna Ishola; Amosun, Olayemi Oluwadamilola; Akinyele, Babatunde Olufemi (International Journal of Finance Research, 2020)
This paper assessed Lift above Poverty Organization (LAPO), rural-women financial security as means of crime reduction Lagos State, women are involved in entrepreneurship to avert criminalities like arm-robbery, kidnapping, cultism, online fraud, terrorism and other security challenge. The study employed cross sectional survey design and was descriptive, combining both qualitative and quantitative techniques. The secondary data were obtained through content analysis of journals, books and online resources. The data were analyzed with Statistical Package for Social Sciences version 20.0. Findings showed that 100% of the respondents were females, 72% of the respondents used credit facilities from LAPO for investments.